EXPLORING THE SIGNIFICANT FACTORS IN ENGAGING SOLAR ENERGY APPLICATION FOR CHILDREN HOME IN PERAK: A CASE STUDY OF SULTAN ABDUL AZIZ CHILDREN HOME IN KUALA KANGSAR, PERAK - Nur Sahida Abdul Rahman; Nur Azfahani Ahmad (Journal of Islamic, Social, Economics and Development, 2021)
People in Malaysia is unaware of the situation that electricity fossil-based resources may be depleted in the future due to its rapid consumption. From rapid development in Malaysia, it is shown that Malaysia will continues to consume a large amount of electricity in the near future that will decrease the resources of fossil fuel. At the moment, Malaysian are lack on information and knowledge regarding the essential of renewable energy that can represent as a supplement power for electricity. Frequent blackouts can also occur in the future if the non-renewable resources deplete. It also can happen to many charity homes in Malaysia that used the main power supply for their electricity. Most charity homes in Malaysia are responsible to acts as a shelter for children in Malaysia which depended on supplied electricity from the main utility, which may face power blackouts from time to time. Therefore, it is necessary to find a solution to overcome this situation by using renewable energy. The most accessible renewable energy that can be gained in Malaysia is solar energy. Therefore, it is wise to propose sustainable energy consumption for Children's Home in Malaysia which is based on the application of solar energy. The aim of this research is to explore the establishment of solar energy applications as supplement energy for electricity for children's homes in Perak, Malaysia. The focus of this study is to encourage people in Malaysia, especially at the level of non-government organisation (NGO) to cultivate awareness of energy and to use energy generated from solar energy in the near future.